Should revolving-door lobbyism in Denmark be regulated? - Blach-Ørsten , Mark; Mayerhöffer, Eva (Politica, 2020)
The revolving door between politics and lobbyism is growing in Denmark without this leading to any new legislation. In several countries, with which Denmark usually compares, similar developments have led to new legislation. The legislation is justified by two general considerations: protection of public trust in the political system and protection of the economic interest of the state. The article describes the rise of revolving-door lobbyism in the Nordic countries and Germany and analyzes recent legislation regulating the revolving door. It is concluded that both public trust and the economic interest of the state are mentioned as arguments for regulation. Against this backdrop, regulation of revolving-door lobbyism in Denmark is discussed.